2017
DOI: 10.1002/cncr.31080
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variations in postmastectomy radiation therapy for breast cancer in patients with 1 to 3 positive lymph nodes: A National Cancer Data Base analysis

Abstract: The receipt of PMRT by patients with breast cancer who have 1 to 3 positive lymph nodes has increased over time, with wide variability in practice patterns in the United States. Cancer 2018;124:482-90. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Compared to previous population-based analyses showing between 30.3% and 40.5% of patients with N1 disease (1-3 positive lymph nodes) receiving PMRT by 2012 [5,6], in our study, 64.7% of such patients were recommended for PMRT. This con rms the trend of an increasing number of patients with N1 disease being considered for PMRT and it is in keeping with national clinical guidelines [7][8][9].…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Compared to previous population-based analyses showing between 30.3% and 40.5% of patients with N1 disease (1-3 positive lymph nodes) receiving PMRT by 2012 [5,6], in our study, 64.7% of such patients were recommended for PMRT. This con rms the trend of an increasing number of patients with N1 disease being considered for PMRT and it is in keeping with national clinical guidelines [7][8][9].…”
Section: Discussioncontrasting
confidence: 84%
“…This highlights some interesting geographical variation, which merits further investigation. A similar US-based study found that density of radiation oncology practices was associated with receipt of PMRT in patients with N1 stage breast cancer [5]. Results of the Selective Use of Post Mastectomy Radiotherapy (SUPREMO) trial are awaited and are likely to reduce the variation in practice of PMRT use in intermediate-risk breast cancer (de ned as pT1-2N1; pT3N0; or pT2N0 if also grade III or with lymphovascular invasion) [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 showing that RLNR rates increased from 19.1% in 2003 to 30.3% for patients with 1-3 positive LNs after mastectomy. 9 The trade-offs of RLNR are increased risks of radiation pneumonitis and BCRL. [10][11][12] Therefore, individualizing treatment decisions regarding axillary surgery (ALND v SLNB), with or without RLNR, is a crucial part of clinical decision making impacting all disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, more recent studies have demonstrated that PMRT following immediate breast reconstruction has acceptable aesthetic outcomes and complication rates, possibly due to improvements in radiation and surgical techniques (Billig et al, 2017; Ho et al, 2017; Mirzabeigi et al, 2013; Shammas et al, 2019). As a result, the use of immediate breast reconstruction has risen, despite concurrent increased use of PMRT and RNI (Ohri et al, 2018; Surgeons ASoP, 2018).…”
Section: Introductionmentioning
confidence: 99%